The HbCO Concentration on Blood of Motorcycle Mechanic Workshop in Surabaya - A Cross-Sectional Study - Ayuningtyas, Citra (JURNAL KESEHATAN LINGKUNGAN, 2019)
Carbon monoxide was one of the indicators of air pollution that most often comes from motor vehicles. Indirectly, increasing the number of motorcycles would be followed by an increase in the number of workshops that provide maintenance services. The process of maintenance and repair in the workshop causes carbon monoxide (CO) levels in the air to be higher from the standard so it was easily inhaled by workers and the internal mechanism reacts became carboxyhemoglobin (HbCO). This study aims to analyze the effect of CO levels in the workshop air and smoking habits of workers on HbCO levels in the blood of workshop mechanic workers. This research was an observational analytic study with 18 respondents as workshop mechanic workers who were male. Respondents in this study were identified based on age, years of service, length of work, use of Personal Protective Equipment (PPE), and nutritional status. The results showed that most respondents aged 25-36 years -old (38,9%), had a year of service â‰¥ 5 years (55,6%), had smoking habits (72,2%), did not use PPE (88,9%) and had a normal nutritional status (47,2%). CO levels in the air had a significant correlation on HbCO levels (p <0,000) as well as smoking habits also had a significant correlation on HbCO levels (p <0,000). It was recommended for workers to reduce smoking habits, improved healthy lifestyles, and used masks to reduce exposure to pollutants.